LOYALITAS MEMODERASI HUBUNGAN MOTIVASI DAN PELATIHAN ISLAMI TERHADAP KINERJA KARYAWAN DI BANK SYARIAH INDONESIA (BSI) - Kurnia, Cindy; Harun, Ubay; Riefma Hidayah, Noor (JARIYAH: JURNAL ILMU AKUNTANSI DAN KEUANGAN SYARIAH, 2025)
Motivation is the basic drive that moves someone or the desire to devote all their energy because of a certain goal. Motivation and training are a series of attitudes and values that influence individual performance. These attitudes and values are invisible forces that encourage individuals to foster employee loyalty. The purpose of this research is to determine the influence of motivation and Islamic training on employee performance with loyalty as a moderating variable. The research uses a quantitative approach, with the research sample consisting of 40 employees from the BSI unit in Tondo village. Data collection was conducted by distributing questionnaires. The analysis technique used multiple regression with the Moderated Regression Analysis (MRA) method to determine the relationship between motivation and Islamic training with loyalty as the moderating variable. The research results show that motivation and Islamic training have a positive effect on employee performance. Loyalty strengthens the relationship between motivation and Islamic training on employee performance.